The Effect Of Work Life Balance And Organizational Commitment On Turnover Intention With Job Satisfaction As Mediation Variable - Permatasari, Fanny; Sugiarto, Agus (Jurnal Ekonomi, 2024)
This study aims to determine the effect of work-life balance and organizational commitment on turnover intention with job satisfaction as a mediator in the study of PT BPR BKK Boyolali. The sample technique in this study uses cluster sampling, which is a method based on area or cluster. This study used a sample of 125 respondents. The data collection technique in this study used a questionnaire distributed via Google Form. This study uses data analysis techniques carried out by the Partial Least Square (PLS) method using SmartPLS version 3.0 software. This study shows different results from previous studies with the addition of a new variable, namely job satisfaction as a mediating variable. The results showed that work-life balance has no effect on turnover intention, organizational commitment has a negative effect on turnover intention, work-life balance has a positive effect on job satisfaction, organizational commitment has a positive effect on job satisfaction, job satisfaction has no effect on turnover intention, job satisfaction does not mediate the effect of work-life balance on turnover intention, job satisfaction does not mediate the effect of organizational commitment on turnover intention. Then the limitations in this study are the characteristics of employees in terms of age and certain length of service. Therefore, it is hoped that future researchers can add other variables and expand the research object to different fields and agencies